GAMBARAN BEBERAPA FAKTOR TERKAIT PEMANFAATAN BED OCCUPANCY RATE (BOR) DI RUMAH SAKIT UMUM DAERAH dr. R. KOESMA KABUPATEN TUBAN - Tri Bintari Putri; Yudhy Dharmawan; Sri Winarni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
BOR indicators is an important indicator to determine the level of hospital services that are used by hospital management. The purpose of this study is to describe the factors related to the utilization of bed occupancy rate (BOR) in RPH of sr. R. Koesma Tuban. This research is explanatory research with quantitative-qualitative method. The population of this research are all heads of the wards in dr. R. Koesma Tuban. The sample of this research is total population of 12 persons chief of inpatient room, 1 person chief of nursing hospitalization, and 1 deputy director of field services. The results of the univariate study shows the percentage of knowledge (78.6%), the percentage of completeness data collection (70.93%), the percentage of utilization of the data (37.5%). Planning for energy needs, infrastructure, mapping hospitalization, and finance are obtained from Regional Revenue and Expenditure Budget, State Revenue and Expenditure Budget, fund hospital. Human resources are still lacking for some of the wards and no reward in the utilization BOR. Suggestion from the researcher to chief the nursing hospitalization are to provide education and training related to the daily inpatient room census filling, prepare standard operating procedures on the utilization of BOR for chief of the ward, and give rewards to the ward.